Upaya Meningkatkan Hasil Belajar Akidah Akhlak Materi Q.S Al-Hujurat/49:13 dengan Pemanfaatan Model True or False - Yanti (GHIROH, 2023)
This article is focused on determining the improvement in student learning outcomes through the application of the true or false learning model on the material of Al Hujurat: 13 in class V MIS Baserah, Kuantan Sengingi Regency. The subjects of this classroom action research were 13 class V students of MIS Baserah, Kuantan Sengingi Regency, consisting of 7 men and 6 women who came from different backgrounds. The research used in this report is Classroom Action Research. Based on the research results, there was an increase in student learning outcomes on Surah Al Hujurat: 13 after taking action using the true or false model compared to before the action. The results of the research can make a positive contribution to teachers of Aqidah Akhlak subjects in particular and the world of education in general.